Computational modeling of fabrication of nanoneedle based on multi-physics analysis. (2nd January 2020) - Zhang, Linan; Guo, Ziwang; Wu, Liqun; Chen, Chao
Abstract: A three-dimensional model for fabrication process of Ag2 Ga nanoneedle based on phase field model has been performed. With the development of model, the fabrication of Ag2 Ga nanoneedle which is induced by chemical reaction has been well presented. The model incorporates a number of components, such as silver and gallium, which plays a crucial role in the diffuse and chemical reaction process. A phase field model is employed to describe the fabrication process and then supply reliable information to control the morphological evolution of Ag2 Ga nanoneedle. The purpose of this work is providing a reliable mechanism of fabrication process of Ag2 Ga nanoneedle in room temperature, and control the structure of nanoneedle in different temporal perspectives.